IDIS Small Bodies and Dust Node: Technical innovation and science. Issue 2 (15th January 2015) - Giardino, M.; Braga, V.F.; De Sanctis, M.C.; Giacomini, L.; Giuppi, S.; Turrini, D.; Capria, M.T.
Abstract: It is not trivial, nowadays, to be fully aware of the impressive amount of astrophysical resources that are at hand. Virtual Observatories (VOs) were therefore created to provide a simple access to what astronomers look for. In this paper we focus on the original data access services developed specifically, in a VO perspective, for the "Small Bodies and Dust Node" (SBDN) in the framework of the Integrated and Distributed Information System (IDIS) initiative of the Europlanet Research Infrastructure project. We describe the scientific goals, along with the innovative technical aspects, of the tools that SBDN presently provides to the scientific community, namely the Comet Emission Lines service, and the Cosmic Dust Catalog service. In the former, an algorithm for the detection of unidentified emission lines has been implemented.